A Persistent Threat The Evolution of al Qa'ida and Other Salafi Jihadists - Jones, Seth G. (RAND Corporation, 2014)
This report examines the status and evolution of al Qa'ida and other Salafi-jihadist groups, and uses qualitative and quantitative data to assess whether this movement has strengthened. The author uses this analysis to examine U.S. strategic options to counter al Qa'ida and other terrorist groups based on the threat level and the capacity of local governments.